A New Direct Coupling Method for Photovoltaic Module‐PEM Electrolyzer Stack for Hydrogen Production. Issue 4 (19th June 2018) - Yang, Z.; Lin, J.; Zhang, H.; Lin, B.; Lin, G.
Abstract: A direct coupling hydrogen production system consisting of a photovoltaic (PV) cell and a proton exchange membrane (PEM) electrolyzer is established. The expression of the hydrogen production efficiency is derived and the general performance characteristics are revealed. The number of series‐parallel connected PV cell is optimized using the hydrogen production effficiency of the system as objection function. The maximum efficiency and the corresponding optimal values of the number of series‐parallel connected PV cell are obtained. In contrast to optimize the number of series‐parallel connected electrolyzer, a simple and efficent method is proposed. The effects of some important performance parameters, such as types of the solar cells, solar irradiance, and leakage resistance of the electrolyzer stacks on the hydrogen production efficiency of the direct coupling system are examined in detail. It is found that the proposed optimal coupling approach can efficiently improve the hydrogen production efficiency. Moreover, the maximum hydrogen production efficiency of the direct coupling system using the Si solar cell is higher than that of the one using the GdTe and AsGa solar cells. Finally, the hydrogen production efficiency increases as the leakage resistance increases.